Numerical comparison of methods for solving second-order ordinary initial value problems - Al-Khaled, Kamel; Anwar, M. Naim (Applied mathematical modelling, 2007)
In this paper, we apply Adomian decomposition method (shortly, ADM) to develop a fast and accurate algorithm of a special second-order ordinary initial value problems. The ADM does not require discretization and consequently of massive computations. This paper is particularly concerned with the ADM and the results obtained are compared with previously known results using the Quintic C 2-spline integration methods. The numerical results demonstrate that the ADM is relatively accurate and easily implemented.